2009
DOI: 10.1007/s11920-009-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of reading disability

Abstract: Genetic factors contribute substantially to the development of reading disability (RD). Family linkage studies have implicated many chromosomal regions containing RD susceptibility genes, of which putative loci at 1p34-p36 (DYX8), 2p (DYX3), 6p21.3 (DYX2), and 15q21 (DYX1) have been frequently replicated, whereas those at 3p12-q12 (DYX5), 6q13-q16 (DYX4), 11p15 (DYX7), 18p11 (DYX6), and Xq27 (DYX9) have less evidence. Association studies of positional candidate genes have implicated DCDC2 and KIAA0319 in DYX2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…We found that 10 of the 14 dyslexia candidate genes that were suggested by the literature had been shown to directly or indirectly interact and could be integrated into a molecular signaling network contributing to dyslexia etiology, responsible for regulating neuronal migration and neurite outgrowth. Our work builds on findings of other researchers in the field of dyslexia genetics, 5,[11][12][13] as well as existing knowledge about genes involved in neuronal migration disorders and the KEGG pathway for axon guidance (http:// www.genome.jp/dbget-bin/show_pathway?map043600). Moreover, based on the signaling network, we propose three novel dyslexia candidate genes from linkage regions.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…We found that 10 of the 14 dyslexia candidate genes that were suggested by the literature had been shown to directly or indirectly interact and could be integrated into a molecular signaling network contributing to dyslexia etiology, responsible for regulating neuronal migration and neurite outgrowth. Our work builds on findings of other researchers in the field of dyslexia genetics, 5,[11][12][13] as well as existing knowledge about genes involved in neuronal migration disorders and the KEGG pathway for axon guidance (http:// www.genome.jp/dbget-bin/show_pathway?map043600). Moreover, based on the signaling network, we propose three novel dyslexia candidate genes from linkage regions.…”
Section: Introductionmentioning
confidence: 94%
“…Considerable effort has been spent in trying to identify the dyslexia genes in a number of these regions by conducting candidate gene association studies, which will be discussed below and in Tables 2 and 3. For additional reviews of the candidate gene association literature of dyslexia, we also refer to Petryshen and Pauls, 5 Scerri and Schulte-Korne 8 and Schumacher et al 40 Until now, no genome-wide association studies (GWAS) for developmental dyslexia have been published. However, Meaburn et al 41 reported a GWAS of early reading (dis)ability in the general population using a quantitative trait loci approach.…”
Section: Linkage and Association Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…it is believed that several genes with modest effect sizes contribute to this multi-factorial phenotype affecting 5-10% of school-aged children (Katusic et al 2001;Shaywitz et al 1990). Several candidate genes are described for dyslexia (Smiths 2007;Caylak 2007) and there is evidence for DYX1C1, ROBO1, DCDC2 and KIAA0319 in regulation of neuronal migration, neurite outgrowth and axon pathfinding (Petryshen and Pauls 2009;Poelmans et al 2010). The first candidate gene described for dyslexia, DYX1C1, is the most studied functionally with regards to its role in dyslexia.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%